The effect of overtime regulations on employment - Ronald L. Oaxaca; Galiya Sagyndykova (IZA World of Labor, 2020)
Regulation of standard workweek hours and overtime hours and pay can protect workers who might otherwise be required to work more than they would like to at the going rate. By discouraging the use of overtime, such regulation can increase the standard hourly wage of some workers and encourage work sharing that increases employment, with particular advantages for female workers. However, regulation of overtime raises employment costs, setting in motion economic forces that can limit, neutralize, or even reduce employment. And increasing the coverage of overtime pay regulations has little effect on the share of workers who work overtime or on weekly overtime hours per worker.
Keywords: J38; J68; J88; 330; overtime; wages; labor demand; employment